Assessing the impacts of COVID-19 on Myanmar’s economy: A Social Accounting Matrix (SAM) multiplier approach - Diao, Xinshen; Aung, Nilar; Lwin, Wuit Yi; Zone, Phoo Pye; Nyunt, Khin Maung; Thurlow, James (International Food Policy Research Institute, 2020)
The measures taken by the Government of Myanmar to contain the transmission of COVID-19 are a necessary and appropriate response. In-depth analysis of measures of this magnitude on firms, households, government, and the economy as a whole is key to the design of policy interventions that can mitigate the economic losses and support a sustained and robust recovery. The economic losses to Myanmar’s economy in 2020 due to the COVID-19 pandemic will be huge – a drop in production on the order of between 6.4 and 9.0 trillion Kyat – and likely will push the economy into a recession or lead to stagnant growth, at best, for the year. Although lockdown policies provide exemptions for most agricultural activities, linkages to other sectors indirectly affect the agri-food sector significantly. The agricultural sector is expected to contract by between 1.1 and 2.4 percent in 2020, and recovery will be slow. Closure of factories will have a large negative economic impact due to the strong linkage effects between manufacturing and upstream primary agriculture and downstream marketing services. Reopening the manufacturing sector is crucial for economic recovery in Myanmar.